In-Line Aerosol Therapy via Nasal Cannula during Adult and Paediatric Normal, Obstructive, and Restrictive Breathing - Marc Mac Giolla Eain; Ronan MacLoughlin (MDPI AG, 2023)
High-flow nasal oxygen therapy is being increasingly adopted in intensive and home care settings. The concurrent delivery of aerosolised therapeutics allows for the targeted treatment of respiratory illnesses. This study examined in-line aerosol therapy via a nasal cannula to simulated adult and paediatric models with healthy, obstructive and restrictive lung types. The Aerogen Solo vibrating mesh nebuliser was used in combination with the InspiredTM O2FLO high-flow therapy system. Representative adult and paediatric head models were connected to a breathing simulator, which replicated several different states of lung health. The aerosol delivery was quantified at the tracheal level using UV-spectrophotometry. Testing was performed at a range of supplemental gas flow rates applicable to both models. Positive end-expiratory pressure was measured pre-, during and post-nebulisation. The increases in supplemental gas flow rates resulted in a decrease in aerosol delivery, irrespective of lung health. Large tidal volumes and extended inspiratory phases were associated with the greatest aerosol delivery. Gas flow to inspiratory flow ratios of 0.29-0.5 were found to be optimum for aerosol delivery. To enhance aerosol delivery to patients receiving high-flow nasal oxygen therapy, respiratory therapists should keep supplemental gas-flow rates below the inspiratory flow of the patient.